Residential satisfaction: concept, theories and empirical studies - Mohit, Mohammad Abdul; Al-Khanbashi, Adel Mahfoud Mubarak (Malaysian Institute of Planners, 2014)
Residential satisfaction, defined as the feeling of contentment when one has or achieves what one needs or desires in a house, is an important indicator and planners, architects, developers and policy makers use it in a number of ways. There are three theories – housing needs theory, housing deficit theory and psychological construct theory, and most empirical studies have used these theories or a combination of these theories in their research design. A number of variables representing housing and neighbourhood characteristics, individuals‘ socio-demographic attributes as well as their perceptions of housing and neighbourhood conditions have been analysed in most empirical studies what stand to indicate that further studies are required until a general theory of residential satisfaction/ dissatisfaction emerges. Also, a host of variables belonging to housing and its environment including the sociodemographic attributes of residents exert significant influences on the level of residential satisfaction/ dissatisfaction which is however, culture and value specific indicating that further studies on residential satisfaction/ dissatisfaction can be undertaken on case specific context to guide public policies on housing.